Estimation of stability derivatives in newtonian limit for oscillating cone - Shabana, Aysha; Monis, Renita Sharon; Crasta, Asha; Khan, Sher Afghan (Institute of Physics Publishing, 2018)
Stability derivatives in Newtonian limit for an oscillating cone are obtained. Stiffness derivative decreases with pivot position for the entire range of cone angles. For cone angles in the range 20 to 30 degrees there is substantial increase in the stiffness derivative. Damping derivative decreases with pivot position for various cone angles and attains a minima at h = 0.75 and then again with increase in pivot position there is non-linear increment in damping derivatives. There is considerable change in the magnitude, for higher cone angles in the range of 20 degrees and above as the centre of pressure has further moved towards the trailing edge of the cone at pivot position around h = 0.88. Stiffness derivative increases with cone angle for various pivot positions. Damping derivative with cone angle for various fixed pivot positions is seen to increase linearly with cone angle, it is also observed that this trend of linear increment tend to become non-linear for cone angles in the range 20 degrees and beyond. Damping derivative decreases with pivot position h = 0.8 for the entire range of cone angles, however, for pivot position h = 1.0, shows almost constant values up to cone angle of 20 degrees. For cone angle 30 degrees value of damping derivative coincides irrespective of pivot position being at h = 0.8 or 1.0 and this trend is attributed to the 3-D effect of the flow field.